2004
DOI: 10.3346/jkms.2004.19.6.874
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pressure Pain Threshold, Grip Strength, Dexterity and Touch Pressure of Dominant and Non-Dominant Hands within and Between Right- and Left-Handed Subjects

Abstract: This study was done to evaluate differences in pressure pain threshold, grip strength, manual dexterity and touch pressure threshold in the dominant and non-dominant hands of right- and left-handed subjects, and to compare findings within and between these groups. Thirty-nine right-handed and twenty-one left-handed subjects participated in the study. Pressure pain threshold was assessed using a dolorimeter, grip strength was assessed with a hand-grip dynamometer, manual dexterity was evaluated using the VALPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 15 publications
7
67
2
2
Order By: Relevance
“…In addition, no difference between muscle strength and manual dexterity variables for the dominant and non-dominant upper limbs was observed. These results differ from those described in the literature, which has shown that the dominant member is able to develop higher levels of muscle strength and has a better performance on tasks that require manual dexterity in relation to the non-dominant member (Lima et al, 2012;Lima et al, 2011;Ozcan et al, 2004).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In addition, no difference between muscle strength and manual dexterity variables for the dominant and non-dominant upper limbs was observed. These results differ from those described in the literature, which has shown that the dominant member is able to develop higher levels of muscle strength and has a better performance on tasks that require manual dexterity in relation to the non-dominant member (Lima et al, 2012;Lima et al, 2011;Ozcan et al, 2004).…”
Section: Discussioncontrasting
confidence: 57%
“…In those tasks, better performance of the dominant upper limb has been observed (Lima et al, 2012;Lima, Santos, & de Freitas, 2011;Ozcan et al, 2004). The association between strength and dexterity in aiming movement performance of the right and left sides was not examined in these studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, no information considering menstrual cycle phase was obtained in the present experiment, though there are some indications 27 that this is also a factor that affects pain sensitivity. Additionally, participants were not asked if they were left-or right-handed though, according to some authors 30 , dexterity might influence hand-sensitivity. Also, since familiarity of pain modalities turned out to be a possible confounding variable, further studies should include at least several pre-measurements (that would not be taken into the statistical analysis) in order to reduce or eliminate its possible effect.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Manual dexterity is defined as the ability to integrate precision and speed with finely coordinated movements of the arm, hand and fingers [3]. Skilled movement requires complex patterns of muscular coordination based on motor patterns acquired during early life [4].…”
Section: Introductionmentioning
confidence: 99%